The art of loving Krishna : ornamentation and devotion - Packert, Cynthia (Indiana University Press, 2010)
Since ancient times, Hindus have expressed their love and devotion to their deities through beautiful ornamentation -- dressing and decorating the deities with elaborate clothing, jewelry, and flowers. In this pioneering study of temples in Vrindaban and Jaipur, India, Cynthia Packert takes readers across temple thresholds and into the god Krishna's sacred domain. She describes what devotees see when they behold gorgeously attired representations of the god and why these images look the way they do. She d.